Inhibition of Protein Kinase CK2 Prevents Adipogenic Differentiation of Mesenchymal Stem Cells Like C3H/10T1/2 Cells - Lisa Schwind; Sarah Schetting; Mathias Montenarh (MDPI AG, 2017)
Protein kinase CK2 as a holoenzyme is composed of two catalytic α- or α'-subunits and two non-catalytic β-subunits. Knock-out experiments revealed that CK2α and CK2β are required for embryonic development. Little is known about the role of CK2 during differentiation of stem cells. Mesenchymal stem cells (MSCs) are multipotent cells which can be differentiated into adipocytes in vitro. Thus, MSCs and in particular C3H/10T1/2 cells are excellent tools to study a possible role of CK2 in adipogenesis. We found downregulation of the CK2 catalytic subunits as well as a decrease in CK2 kinase activity with progression of differentiation. Inhibition of CK2 using the potent inhibitor CX-4945 impeded differentiation of C3H/10T1/2 cells into adipocytes. The inhibited cells lacked the observed decrease in CK2 expression, but showed a constant expression of all three CK2 subunits. Furthermore, inhibition of CK2 resulted in decreased cell proliferation in the early differentiation phase. Analysis of the main signaling cascade revealed an elevated expression of C/EBPβ and C/EBPδ and reduced expression of the adipogenic master regulators C/EBPα and PPARγ2. Thus, CK2 seems to be implicated in the regulation of different steps early in the adipogenic differentiation of MSC.